Pengaruh Model Pembelajaran Teams Games Tournament (TGT) Berbantuan Media Monopoli Matematika (MONIKA) Terhadap Kemampuan Menghitung Keliling Dan Luas Bangun DatarKEMAMPUAN MENGHITUNG KELILING DAN LUAS BANGUN DATA - Puspitasari, Mei (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the Teams Games Tournament learning model assisted by the Mathematical Monopoly (MONIKA) media on the ability to calculate the perimeter and area of flat shapes for fourth grade students. This research is a type of Pre-Experimental Design research, with the One Group Pretest-Posttest Design model. The samples taken were 20 students who were used as the experimental class. The sampling technique used was saturated sampling. Data collection using the test method. This test is used to measure the extent to which students are able to calculate the circumference and area of flat shapes before and after being given treatment. The analysis used in this study is the Wilcoxon Signed Rank Test with the SPSS version 25.0 program. The results showed that the Teams Games Tournament learning model assisted by the Mathematical Monopoly (MONIKA) media had an effect on the ability to calculate the circumference and area of flat shapes. Evidence of an increase in students' ability to calculate the circumference and area of flat shapes is that there is a significant difference between the pretest and posttest scores, namely the pretest average value of 50.88, while the posttest average value of 70.55. This is supported by the existence of a hypothesis test carried out with the Wilcoxon Signed Rank Test, the Asymp. Sig. (2-tailed) of 0.000 (0.000 < 0.005). Based on the results of the analysis and discussion, there was an increase of 19.67 from the average pretest and posttest results. The results of the study can be concluded that the use of the Teams Games Tournament learning model assisted by the Mathematical Monopoly (MONIKA) media has a significant effect on the ability to calculate the circumference and area of flat shapes.